2012
DOI: 10.1115/1.4005850
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Shear-Based Hemolysis Caused by Renal Obstruction

Abstract: As endovascular treatment of abdominal aortic aneurysms (AAAs) gains popularity, it is becoming possible to treat certain challenging aneurysmal anatomies with endografts relying on suprarenal fixation. In such anatomies, the bare struts of the device may be placed across the renal artery ostia, causing partial obstruction to renal artery blood flow. Computational fluid dynamics (CFD) was used to simulate blood flow from the aorta to the renal arteries, utilizing patient-specific boundary conditions, in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…An increase in WSS was found only close to the stent struts. 19 An intended lower positioning of the EVAS stents in this study may have improved the renal flow profile, and this will be the subject of a future study. That position, however, could reduce the sealing zone and thus increase the risk of other problems, including migration and type IA endoleak.…”
Section: Discussionmentioning
confidence: 91%
“…An increase in WSS was found only close to the stent struts. 19 An intended lower positioning of the EVAS stents in this study may have improved the renal flow profile, and this will be the subject of a future study. That position, however, could reduce the sealing zone and thus increase the risk of other problems, including migration and type IA endoleak.…”
Section: Discussionmentioning
confidence: 91%
“…Along with the above-mentioned in vitro and in vivo investigations, several computational fluid dynamics (CFD) studies have been also undertaken to investigate the role of haemodynamic forces in the progression of ARAS (Ku et al 1989;Cheer et al 1998;Yim et al 2004;Hassani et al 2007;Kagadis et al 2008;Segalova et al 2012;Albert et al 2014;Zhang et al 2014). All these studies have confirmed the inevitable roles of haemodynamic parameters and anatomic and physiological features of the renal artery bifurcation in the progression of ARAS.…”
Section: Introductionmentioning
confidence: 85%
“…This phenomenon was also observed in a previous flow study on EVAS with the 28-mm IFU model, 26 showing that maximum shear rate associated with this increase in peak velocity in the RA is well below the pathological threshold for acute thrombosis, so this event should not be expected. 26 The computational fluid dynamics study conducted by Segalova and coauthors 27 has demonstrated that the proximal bare stent had almost no influence on the renal flow profile when positioned across the RA orifice, and it is not likely that the proximal bare metal stent will cause large disturbances in RA flow profile. An intended positioning with the bare metal stent across the RA ostium (proximal 4 mm) should be a safe margin for positioning of the endosystem with reference to the RA orifice.…”
Section: Discussionmentioning
confidence: 99%